EFFECT OF A DIETARY INTERVENTION ON GROWTH AND ENERGY EXPENDITURE IN CHILDREN WITH CYSTIC FIBROSIS - Groleau, Veronique (2014)
BACKGROUND: The study aim was to determine the effect of a dietary intervention on growth, body composition and resting energy expenditure (REE) in children with cystic fibrosis (CF) and pancreatic insufficiency (PI) in a randomized, double blind, placebo-controlled trial. METHODS: Subjects (5 to 17 yrs) participated in a 12-month trial of the organized lipid matrix LYM-X-SORB™ (LXS) vs. placebo dietary supplements with similar calories, total fat and fatty acids. Dietary intake was assessed using 3-day weighed food records. Height (HAZ), weight (WAZ), BMI (BMIZ), mid-upper arm muscle (UAMAZ) and fat area (UAFAZ) Z-scores were calculated. Fat mass (FM) and fat free mass (FFM) were obtained by whole body DXA. REE (kcal/d) was evaluated by indirect calorimetry at baseline, 3 and 12 months and %REE calculated using Schofield equations. No growth or REE differences were observed between LXS and placebo groups so data were pooled for analysis. RESULTS: 63 children (57% males, age 10.6±2.9 yr, 43% receiving LXS) completed REE measurements. Caloric intake increased from a median of 2502 [1478, 4909] to 2616 [1660, 4125] kcal/d at 12 months. HAZ, WAZ and UAMAZ increased (p < 0.05) over 12 months. Mean REE was 109±8% predicted at baseline and 107±9% at 12 months (p < 0.05). REE (kcal/d) adjusted for FFM and FM decreased over 12 months ([mean±SE] −31±12 kcals, p < 0.01), significant only in males (−49±16 kcals, p < 0.01). CONCLUSIONS: Over a 12 month nutrition intervention with either LXS or placebo, the growth status, muscle stores and REE improved. Sustained increased energy intake improved energy metabolism, growth and nutritional status in school age children with CF, PI and mild lung disease.